Psychiatry and innovative technologies - Latas, Milan (Engrami, 2024)
This paper presents achievements in the application of innovative technologies in the field of psychiatry. Technologies such as artificial intelligence (AI), machine learning, telepsychiatry and digital therapy tools have significantly changed the approach to diagnosis and treatment of mental disorders. The paper analyzes the advantages, challenges, and ethical implications of the use of these technologies, and explores their impact on the future of psychiatry.
Keywords: psychiatry, technology, artificial intelligence, machine learning, telepsychiatry